ORGANIZED GEM AND JEWELLERY RETAILERS STORE IMAGE COMPONENTS – CONCEPTUAL - K. Balaji; Benny, Ashley Dominic; S. Lakshminarayanan (ShodhKosh: Journal of Visual and Performing Arts, 2022)
This research paves way for understanding India’s retail industry at present, the growth of organized retailers in Gem and Jewellery industry with reference to India, the concept of store image and its formation components in a broader way. Many researches have been done on identifying the store image attributes from shoppers perspective. This research is different in terms of identifying the store image formation component conceptually. To cover the store image research under retailing it is necessary to find the components in a broader way. Doing an extensive literature review it is found that store image formation is beyond functional and psychological. To conclude image formation for retailers are based upon Physical, Cognitive, Emotional and Self Image. This study will ignite more empirical research in the field of retailing for managing the store and to create competitive advantage. Further this research paper will help the retailers to overcome the difficulties by limiting the number of store image items into various categories.